2014
DOI: 10.1042/bsr20130124
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evidence that regulation of Ero1β activity in human cells does not involve the isoform-specific cysteine 262

Abstract: In the ER (endoplasmic reticulum) of human cells, disulfide bonds are predominantly generated by the two isoforms of Ero1 (ER oxidoreductin-1): Ero1α and Ero1β. The activity of Ero1α is tightly regulated through the formation of intramolecular disulfide bonds to help ensure balanced ER redox conditions. Ero1β is less tightly regulated, but the molecular details underlying control of activity are not as well characterized as for Ero1α. Ero1β contains an additional cysteine residue (Cys262), which has been sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Other intramolecular disulfide bonds also exist that are implicated in regulation of Ero1p activity [ 175 ]. Similar intra- and intermolecular disulfide-dithiol exchange has been demonstrated for human Ero1α and Ero1β isoforms [ 176 , 177 , 178 ]. Kinetic analysis revealed that formation of the correct regulatory S–S bond within Ero1α in the presence of O 2 or H 2 O 2 is slow, but is significantly enhanced in the presence of PDI family members [ 179 ].…”
Section: Er Oxidoreductins As Key Players In Oxidative Protein Folsupporting
confidence: 52%
“…Other intramolecular disulfide bonds also exist that are implicated in regulation of Ero1p activity [ 175 ]. Similar intra- and intermolecular disulfide-dithiol exchange has been demonstrated for human Ero1α and Ero1β isoforms [ 176 , 177 , 178 ]. Kinetic analysis revealed that formation of the correct regulatory S–S bond within Ero1α in the presence of O 2 or H 2 O 2 is slow, but is significantly enhanced in the presence of PDI family members [ 179 ].…”
Section: Er Oxidoreductins As Key Players In Oxidative Protein Folsupporting
confidence: 52%
“…The Ero1‐Pdi1 module is critical to the formation of disulfide bonds of substrate proteins in yeast and mammals (Anelli et al ., 2002; Vitu et al ., 2010; Hansen et al ., 2014). Considering that FonNst2 exists as dimers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of DTT to the Ero1α complex results in a mix of activated Ero1 states, whereas addition of DTT and GuHCl results in the formation of the fully reduced state. Ero1β is expected to have a free thiol ( Hansen et al, 2014 ); hence, the nonreduced protein was treated with 20 mM NEM to avoid disulfide rearrangement during the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Before rpHPLC analysis, 100 μg of purified Ero1α complex diluted in 500 µl of 20 mM sodium phosphate, pH 7.0, was treated with or without 2 mM DTT or 5.5 M guanidinium chloride plus 2 mM DTT for 15 min at RT. Similarly, 100 μg of Ero1β complex was treated with guanidinium chloride in the presence of either 2 mM DTT or 20 mM NEM to avoid potential disulfide rearrangement with the Ero1β-specific unpaired Cys262 ( Hansen et al, 2014 ). The samples were injected and bound to a μPRC C2/C18 ST 4.6/100 column (Amersham Biosciences) in a mobile phase of 0.1% TFA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation